(untitled) (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Biological Sciences Series, 2026)
Lung cancer represents one of the tum ors most associated with exposure to environmental pollutants such as acrylamide. The aim of this study was to investigate the intravenous protective role of Vit C against pulmonary toxicity and acrylamide-induced cancer. The study included 60 Balb/c mice, distributed equally into 6 groups. Group one: They were given water and food throughout the experiment, Group two: dosed with vitamin C via oral tube feeding, Group three: vitamin C with injected intravenously, Group four: dosed with (AC), Group five: vitamin C was given in conjunction with (AC), Group six: vitamin C was injected simultaneously with AC. At the end of the experiment, the remaining mice from the six groups were sacrificed and a microscopic study of the lung tissue was conducted to observe the changes induced by acrylamide and tested the intravenous protective role of Vit C in reducing these. The results showed the occurrence of severe pulmonary toxicity in group four, while the significant role of intravenous Vit C in the prevention of pulmonary toxicity as an antioxidant was observed in group six.